A path to good jobs? Unemployment and low wages: The distribution of opportunity for young unskilled workers - Robert M. Hutchens (Levy Economics Institute of Bard College, 1994)
Robert M. Hutchens examines three paths by which a young person with limited academic credentials may avoid a life of unemployment and low wages: obtaining additional formal schooling, securing a job that provides secure employment at good wages, or acquiring a job that provides skills and thereby opens a door to good future jobs. He finds that the policy most likely to reduce the supply of unskilled labor would include enhancing early childhood education programs, disbursing training vouchers to young adults, and restricting the immigration of unskilled workers. Owing to the difficulty of identifying jobs, occupations, and industries that would consistently result in financial security for those with limited academic skills, Hutchens concludes that, with few exceptions, demand-side interventions will not work.
Keywords: 330